267 Histopathologic ultrastaging of sentinel lymph nodes in endometrial carcinoma: A retrospective analysis of the tuebingen women's hospital 2006-2016 patient cohort. (13th November 2020) - Baudoux, L; Staebler, A; Greif, K; Krämer, B; Hoffmann, S; Neis, F; Andress, J; Grube, M; Pasternak, J; Taran, F; Krämer, P; Bachmann, C; et al.
Abstract : Introduction: Lymph node metastases are considered a major risk factor in endometrial carcinoma patient management and nodal assessment is an integral part of staging. While still under investigation sentinel node biopsy has been established in many centers. It has been shown that histopathologic ultrastaging leads to an increased detection of isolated tumor cells (ITC) and micrometastases (MIC). However, the clinical impact of ITC and MIC is not yet clearly defined. The aim of this study was to retrospectively perform histopathologic ultrastaging in a large series of endometrial carcinoma patients all of which have been treated at the Tuebingen University Women's Hospital. Method: Patients with sentinel node biopsy during endometrial carcinoma surgery were identified. All cases with negative sentinel nodes, were submitted to retrospective histopathologic ultrastaging (5 × 100μm intervals followed by 500μm sections and immunohistochemical pancytokeratine staining of the entire lymphnode). Results: A total of n=159 cases was available, of which in 5/159 (3.0%) case positive nodes were detected during initial routine pathology workup (pT1a, G3: n=1; pT1b, G1: n=1; pT1b, G3: n=2; pT2, G2: n=1). After retrospective ultrastaging additional micrometastases were identified in n=3 cases (pT1a, G1; pT1a, G2; pT1a, G3), isolated tumor cells in n=2 cases (pT1a, G3; pT1b, G3), a macrometastasis was revealed in one case (pT1b, G3). Overall 11/159 cases (6, 7%) were finally reported positive. Conclusion: In our cohort histopathologic ultrastaging of endometrial carcinoma sentinel nodes led to a substantially increased detection rate of nodes with isolated tumor cells, micro- and macrometastases. We suggest that histopathologic ultrastaging should be mandatory in endometrial carcinoma sentinel lymph node workup.